Early Detection of Left Ventricular Contractility Abnormalities by Two-Dimensional Speckle Tracking Strain in Chagas' Disease - Barbosa, Marcia M; Rocha, Manoel O Costa; Vidigal, Daniel Furtado; de Carvalho Bicalho Carneiro, Renata; Araújo, Rafaela Drumond; Palma, Mariana Campos; de Barros, Marcio Vinicius Lins; Nunes, Maria Carmo P (Echocardiography (Mount Kisco, N.Y.), 2014)
Background Chagas' disease is an important cause of heart failure, and early identification of cardiac involvement may help to identify patients at risk for disease progression. Two‐dimensional (2D) speckle tracking (ST) strain seems to be a useful tool to detect incipient ventricular dysfunction. This study aims to analyze if 2D strain can detect contractility abnormalities in asymptomatic patients with Chagas' disease. Methods Seventy‐eight asymptomatic Chagas' disease patients (46% male; age 44.7 ± 8.6 years) with normal cardiovascular exams and a control group of 38 healthy subjects (58% male; age 44.1 ± 9.2 years) were included in the study. Using 2D strain software, left ventricular (LV) end‐systolic longitudinal, radial, and circumferential strain were measured. Global right ventricular (RV) longitudinal strain was also assessed. Results Echocardiographic parameters of LV systolic and diastolic function were similar between patients and controls. 2D longitudinal strain in the basal inferior, and inferoseptal walls, as well as apical segment of the inferolateral wall were lower in patients compared with controls. 2D radial strain was reduced in several segments of the LV walls as well as the global radial strain. 2D circumferential strain at the basal segment of the anterior wall showed a lower value in patients compared with controls, whereas global circumferential strain was similar between patients and controls. 2D RV strain did not differ between groups. Conclusion In a subgroup of asymptomatic patients with Chagas' disease without evident cardiac involvement, 2D strain was reduced compared with healthy individuals, suggesting incipient LV dysfunction in these patients. 2D ST strain has the potential for detecting early myocardial impairment in the setting of Chagas' disease.